Optimalisasi pelaksanaan journal reading di instalasi gawat darurat melalui pendekatan kotter’s 8-step change model - Silitonga, Ester Mutiara Indah; Hariyati, Roro Tutik Sri; Afriani, Tuti; Wildani, Andi Amalia; Nasri, Khairul (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: The Emergency Department of Hospital X Jakarta faces challenges in developing nurses' critical thinking skills, influenced by time constraints and high workloads. One potential strategy to support nurses' continuous professional development is through structured journal reading activities. However, this activity has not been optimally implemented due to the lack of systematic and documented implementation guidelines. Purpose: To optimize the implementation of journal reading in the emergency department using Kotter's 8-Step Change Model. Method: A case study approach with management function analysis covering the stages of planning, organizing, directing, implementing, and Fish Bone analysis. The framework uses Kotter's 8-step change model approach. The activity was carried out at the Emergency Room of Hospital X Jakarta on June 19–28, 2025. Results: There was an increase in knowledge scores on 80% of the items after the socialization, although challenges still occurred in selecting appropriate articles. The socialization was conducted in a hybrid manner with the participation of 44 nurses and generated positive responses to the existence of Standard Operating Procedures (SOPs). Monitoring of nurses showed an increase in understanding and ability to conduct journal reading according to the guidelines. Conclusion: Implementation of the SOP socialization for journal reading has been proven to improve the quality of journal-based learning. Suggestion: Further mentoring and integration of SOPs into cross-unit nursing professional development programs are needed. Keywords: Emergency Department; Journal Reading; Kotter's 8-Step Change Model Approach. Pendahuluan: Instalasi Gawat Darurat Rumah Sakit X Jakarta menghadapi tantangan dalam mengembangkan keterampilan berpikir kritis perawat, dipengaruhi oleh keterbatasan waktu dan tingginya beban kerja. Salah satu strategi yang potensial untuk mendukung pengembangan profesional berkelanjutan perawat adalah melalui kegiatan journal reading yang terstruktur. Namun, kegiatan ini belum terlaksana secara optimal karena belum adanya acuan pelaksanaan yang sistematis dan terdokumentasi. Tujuan: Untuk mengoptimalisasi pelaksanaan journal reading di instalasi gawat darurat melalui pendekatan kotter’s 8-step change model. Metode: Pendekatan studi kasus dengan analisa fungsi manajemen yang meliputi tahapan perencanaan, pengorganisasian, pengarahan, pelaksanaan, serta analisa Fish Bone. Kerangka kerja menggunakan pendekatan kotter’s 8-step change model. Kegiatan dilaksanakan di Instalasi Gawat Darurat Rumah Sakit X Jakarta pada tanggal 19–28 Juni 2025. Hasil: Terdapat peningkatan skor pengetahuan pada 80% butir soal setelah sosialisasi, meskipun masih ditemukan kendala pada pemilihan artikel yang tepat. Sosialisasi dilakukan secara hybrid dengan partisipasi 44 perawat, dan menghasilkan tanggapan positif terhadap keberadaan Standar Prosedur Operasional (SPO). Monitoring terhadap perawat pelaksana menunjukkan peningkatan pemahaman dan kemampuan dalam melakukan journal reading sesuai panduan. Simpulan: Implementasi sosialisasi SPO journal reading terbukti meningkatkan kualitas pembelajaran berbasis jurnal. Suggestion: Diperlukan pendampingan lanjutan serta integrasi SPO dalam program pengembangan profesional keperawatan lintas unit. Kata Kunci: Instalasi Gawat Darurat; Journal Reading; Pendekatan Kotter’s 8-Step Change Model.